Disciplina escolar y ludopatía en estudiantes del quinto ciclo de la Institución Educativa Nivel Primaria N° 601582 Agustín Rivas Vásquez Tamshiyacu Fernando Lores Tenazoa, Maynas 2023 - Bardales Navarro, Brigitte (2024)
The study aimed to establish a relationship between school discipline and ludopathy among fifth-grade students at the primary level Institution N° 601582 Agustín Rivas Vásquez in Tamshiyacu, Fernando Lores Tenazoa, in 2023. The methodology employed was a non-experimental, cross-sectional, field-based, bivariate, and relational design. The target population consisted of 134 fifth-grade students, for whom a census sampling was conducted, utilizing surveys and questionnaires as data collection methods. The results revealed a significant relationship between school discipline and ludopathy, supported by Kendall's Tau-b statistic, which yielded a calculated value of -0.510 with an approximate significance of 0.001 (p p<0.05). This suggests that a high level of school discipline is significantly associated with a notable decrease in ludopathy among primary school students at the Institution N° 601582 Agustín Rivas Vásquez in Tamshiyacu. In conclusion, the primary findings indicate that fostering school discipline can positively contribute to the prevention and reduction of ludopathy among primary school students.